2019
DOI: 10.1016/j.ijrobp.2018.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Three-Fraction Intracavitary Accelerated Partial Breast Brachytherapy: Early Provider and Patient-Reported Outcomes of a Novel Regimen

Abstract: Purpose/objectives: To report early adverse events and patient-reported outcomes (PROs) of 3fraction intracavitary catheter-based partial breast brachytherapy (ICBB). Materials/methods: Eligible women ≥ 50 years of age with ≤2.5 cm, lymph node negative invasive or in-situ breast cancer underwent breast conserving surgery and placement of a brachytherapy applicator. ICBB was initiated on the second weekday after surgery and prescribed to 21 Gy in three, once daily, fractions. Common Terminology Criteria for Adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 42 publications
1
7
0
5
Order By: Relevance
“…Other studies reported encouraging results of vAPBI in patients presenting low-risk breast cancer and confirmed the safety and the efficiency of this new approach (Table 3) [68, 1923].…”
Section: Discussionsupporting
confidence: 53%
“…Other studies reported encouraging results of vAPBI in patients presenting low-risk breast cancer and confirmed the safety and the efficiency of this new approach (Table 3) [68, 1923].…”
Section: Discussionsupporting
confidence: 53%
“…Infections were seen in 3% of patients and no grade 2 or greater toxicities were noted. 95 At this time, limited data are available comparing external beam and brachytherapy APBI approaches. Stecklein et al 96 compared 3D-CRT APBI to applicator brachytherapy in a prospective series of 281 patients.…”
Section: Ultrashort Partial Breast Irradiationmentioning
confidence: 99%
“…Early data for breast brachytherapy delivered in 1-4 fractions has demonstrated excellent local tumor control and cosmetic outcomes (37,38). The phase II Triumph-T trial showed excellent local tumor control (albeit short median follow up) and breast cosmesis using a 3-fraction breast brachytherapy technique, and a similar 4-fraction regimen had excellent cosmesis with no locoregional recurrences at 6 years (37, 39).…”
Section: Breast Brachytherapymentioning
confidence: 99%
“…Early data for breast brachytherapy delivered in 1 to 4 fractions have demonstrated excellent local tumor control and cosmetic outcomes. 37 , 38 The phase 2 Triumph-T trial showed excellent local tumor control (albeit with a short median follow up) and breast cosmesis using a 3-fraction breast brachytherapy technique, and a similar 4-fraction regimen had excellent cosmesis with no locoregional recurrences at 6 years. 37 , 39 Furthermore, in elderly patients, single-fraction regimens have also demonstrated excellent oncologic outcomes, 40 and a recent study comparing PBI with PBI + hormone therapy or hormone therapy alone in women age >70 years with low-risk, hormone-positive, early stage breast cancer demonstrated that PBI was superior when compliance with hormone therapy was poor, 41 and tested compliance interventions have demonstrated no improvement.…”
Section: Breast Brachytherapymentioning
confidence: 99%